Bibliometric Analysis: Environmental, Social, and Governance in the Public Sector - Nurpratiwi, Tiara; Anggreni, Meilinda; Mariza Syafitri , Twenty (Universitas Indo Global Mandiri, 2025)
This study aims to comprehensively map the global research landscape of Environmental, Social, and Governance (ESG) performance in the public sector and government from 2015 to 2025 using bibliometric analysis. Utilizing data from 231 articles sourced from the Web of Science database and analyzed with R Studio and VOSviewer software, this study identifies publication trends, key contributors, thematic evolution, and research gaps. Key findings reveal a very significant increase in research interest, with an annual growth rate reaching 40.97%. The journal Sustainability emerged as a dominant source, and China leads in publication volume, while countries like Egypt demonstrate high citation impact efficiency. Central themes such as Sustainable Development Goals (SDGs), public sector, and government have evolved towards more specific issues including ESG performance, government subsidies, and the role of local government. Six main thematic clusters were identified, reflecting a focus on core global sustainability concepts, ESG performance in specific country contexts (China), governance (Bangladesh), the 2030 Agenda (Spain), and e-government (India). This study concludes a strong research dynamic and identifies crucial future research areas, including innovative financing mechanisms, SDG localization strategies, analysis of SDG interactions, broader stakeholder roles, climate resilience integration, and the development of long-term impact evaluation methodologies. Keywords: ESG Performance, Public Sector, Bibliometric Analysis, Sustainable Development Goals, Research Trends